2011
DOI: 10.1108/09513571211191798
|View full text |Cite
|
Sign up to set email alerts
|

Carbon footprints and legitimation strategies: symbolism or action?

Abstract: Purpose -Climate change and carbon footprints are among the most urgent concerns facing society and are key issues of corporate responsibility. The purpose of this study is to assess whether Australian companies have adjusted their footprint-related disclosure responses. Adopting a legitimacy perspective, a key aim is to assess whether pragmatic or moral legitimation approaches dominate by determining whether disclosure tends to be more reflective of symbolism or of apparent behaviour. Design/methodology/appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
254
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(279 citation statements)
references
References 42 publications
9
254
2
Order By: Relevance
“…However, this type of exemplification tends to rely on unreliable information. In fact, regardless of the nature of the actions implemented by companies, numerous studies question the quality, usefulness, and comparability of the disclosed environmental data, also in the field of climate performance (e.g., Cowan and Deegan 2011;Green and Li 2012;Hrasky 2012;Kolk et al 2008;Talbot and Boiral 2013). In general, as in the case of sustainability reporting, the disclosure process on climate change issues appears to be influenced more by the logic of public relations than by transparency (Boiral 2013;Unerman et al 2007).…”
Section: Corporate Disclosure On Climate Changementioning
confidence: 99%
See 2 more Smart Citations
“…However, this type of exemplification tends to rely on unreliable information. In fact, regardless of the nature of the actions implemented by companies, numerous studies question the quality, usefulness, and comparability of the disclosed environmental data, also in the field of climate performance (e.g., Cowan and Deegan 2011;Green and Li 2012;Hrasky 2012;Kolk et al 2008;Talbot and Boiral 2013). In general, as in the case of sustainability reporting, the disclosure process on climate change issues appears to be influenced more by the logic of public relations than by transparency (Boiral 2013;Unerman et al 2007).…”
Section: Corporate Disclosure On Climate Changementioning
confidence: 99%
“…The disclosure of climate performance can also be achieved through more specific media, such as the Carbon Disclosure Project (CDP), in which a growing number of FT500 companies participate (Pinkse and Kolk 2009). Regardless of the mode of disclosure used, business decisions in this area are not necessarily motivated by the search for more transparency and accountability (e.g., Dawkins and Fraas 2010;Hrasky 2012;Rankin et al 2011;Reid and Toffel 2009). According to the voluntary disclosure theory, proactive organizations tend to use sustainability reports to demonstrate their commitment and good performance in this area (e.g., Bewley and Li 2000;Clarkson et al 2008).…”
Section: Corporate Disclosure On Climate Changementioning
confidence: 99%
See 1 more Smart Citation
“…Existing research, however, found that companies implement carbon management practices in different ways and to different extents [8][9][10][11][12]. Research links the difference in applied carbon management practices to the various multiple pressures, and current literature distinguishes between internal and external pressures and a company's reaction to these pressures [8,9,13]. For instance, institutions such as Carbon Disclosure Project (CDP) increasingly put pressure on organizations to disclose their carbon related information and companies respond internally to these demands by integrating carbon management practices into their operations, structures and processes [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In corporate circles, the response to these pressures by implementing various carbon management practices is increasingly regarded as a key strategic component for a company's long-term sustainability [5][6][7]. Existing research, however, found that companies implement carbon management practices in different ways and to different extents [8][9][10][11][12]. Research links the difference in applied carbon management practices to the various multiple pressures, and current literature distinguishes between internal and external pressures and a company's reaction to these pressures [8,9,13].…”
Section: Introductionmentioning
confidence: 99%